2020
DOI: 10.1111/tpj.14754
|View full text |Cite
|
Sign up to set email alerts
|

A global survey of the transcriptome of allopolyploid Brassica napus based on single‐molecule long‐read isoform sequencing and Illumina‐based RNA sequencing data

Abstract: SUMMARY Brassica napus is a recent allopolyploid derived from the hybridization of Brassica rapa (ArAr) and Brassica oleracea (CoCo). Because of the high sequence similarity between the An and Cn subgenomes, it is difficult to provide an accurate landscape of the whole transcriptome of B. napus. To overcome this problem, we applied a single‐molecule long‐read isoform sequencing (Iso‐Seq) technique that can produce long reads to explore the complex transcriptome of B. napus at the isoform level. From the Iso‐Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
41
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 45 publications
6
41
1
Order By: Relevance
“…Benchmarking of Universal Single-Copy Orthologs (BUSCO) analysis revealed that the transcriptome assemblies of the two species contain more than 94% of the eudicotyledonous “near-universal single-copy orthologs”. This number is similar to or more than that for transcriptome assemblies of other Brassicaceae (Chandler et al 2020; Yao et al 2020; Fernandez-Pozo et al 2021). Furthermore, we found members of all 16 miRNA families that were found to have originated before the emergence of eudicots and conserved in eudicots (Montes et al 2014).…”
Section: Discussionsupporting
confidence: 71%
“…Benchmarking of Universal Single-Copy Orthologs (BUSCO) analysis revealed that the transcriptome assemblies of the two species contain more than 94% of the eudicotyledonous “near-universal single-copy orthologs”. This number is similar to or more than that for transcriptome assemblies of other Brassicaceae (Chandler et al 2020; Yao et al 2020; Fernandez-Pozo et al 2021). Furthermore, we found members of all 16 miRNA families that were found to have originated before the emergence of eudicots and conserved in eudicots (Montes et al 2014).…”
Section: Discussionsupporting
confidence: 71%
“…We discovered two conserved motifs (AUAAA and UGUA) upstream of the poly(A) cleavage site (Figure 5E); these motifs were also present in maize, red clover (Trifolium pratense L.), sorghum (Sorghum bicolor), Brassica napus, and poplar (Populus alba var. pyramidalis) (Abdel- Ghany et al, 2016;Wang et al, 2016;Chao et al, 2018;Hu et al, 2020;Yao et al, 2020). Additionally, to investigate the preferential nucleotides at the poly(A) cleavage sites, we analyzed the nucleotide composition of 50 downstream and 50 upstream nucleotides at all APA cleavage sites.…”
Section: Polyadenylation Analysis and Identification Of Alternatively Spliced Tissue-specific Genesmentioning
confidence: 99%
“…In addition, it expressed higher in all tissues of ZS9 than in yvl ( Figure 5D ). Apart from qRT-PCR, we further analyze the expression pattern of BnaA03.CHLH using RNA-seq data of Zhongshuang11 tissues (including root, stem, leaf, bud, silique, sepal, ovule, pericarp and callus), previously published by our group ( Li et al 2019 ; Yao et al 2020 ). The transcript abundance level of BnaA03.CHLH in leaf was consistent with the relative expression patterns observed in qRT-PCR (Figure S9).…”
Section: Resultsmentioning
confidence: 99%